SHM_415481_HST_3D Double Edged Shaft-Hole Axe, Fredsgård type - Hagaeus, Thomas; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a Double Edged Shaft-Hole Axe of Fredsgård type (Swedish: Fredsgårdsyxa) from the Swedish Middle Neolithic, collected in Skåne and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=413

Link to Sök I Samlingarna

https://samlingar.shm.se/object/C68A0F7D-893C-463D-A07E-857162BF8113
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Photogrammetry; 3D Model; Museum Object; Dynamic Collections; Swedish Middle Neolithic; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi